Building long-term value: A practical guide to integrating ESG into business strategies - Asep Marfu; Hafid Abbas; Ahman Sya; Agung Purwanto; Nadiroh; Bagus Sumargo; Septantri Shinta Wulandari; Daiman; Christin A. Malaihollo; Syakyakirti; David Tanubrata; Dewi Indah Pratiwi (Sustainable Futures, 2025)
This study aims to examine the impact of key factors—green technology innovation, local community engagement, good corporate governance, and public opinion—on sustainable growth in Indonesia. It also explores the moderating role of public opinion in these relationships. A quantitative approach was employed, using survey data from 387 respondents across West Java, Jakarta, and Banten. The data were analyzed using Structural Equation Modeling (SEM) to test the hypothesized relationships. The results reveal that local community engagement, good corporate governance, and public opinion significantly contribute to sustainable growth. In contrast, green technology innovation had no significant direct impact on sustainable growth, and public opinion did not moderate the relationship between green technology and sustainability. These findings contribute to the understanding of how social and institutional factors drive sustainability in emerging economies. The originality of this research lies in its focus on the Indonesian context, offering insights into how local and institutional dynamics influence sustainable growth in a developing country. By highlighting the importance of community engagement and governance structures, this study suggests that fostering public awareness and strengthening institutional frameworks are crucial for achieving long-term sustainability. Future research could expand the scope to other regions or explore the role of green technology in greater depth.